Sweden : Report on the Observance of Standards and Codes; FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This report reviews the Observance of Standards and Codes on the Financial Action Task Force (FATF) Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) for Sweden. The findings suggest that overall, the Swedish legal requirements in place to combat money laundering and terrorist financing are generally comprehensive. Penalties for money laundering are low, generally charges for predicate offences are pursued, and there have been a limited number of convictions for the money laundering offence.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet